The Glymphatic System: A Novel Therapeutic Target for Stroke Treatment - Lv, Tao; Zhao, Bing; Hu, Qin; Zhang, Xiaohua (Frontiers in Aging Neuroscience, 2021)
Abstract: The glymphatic system (GS) is a novel defined brain-wide perivascular transit network between cerebrospinal fluid (CSF) and interstitial solutes that facilitates the clearance of brain metabolic wastes. The complicated network of the GS consists of the periarterial CSF influx pathway, astrocytes mediated convective transport of fluid and solutes supported by AQP4 water channels and perivenous efflux pathway. Recent researches indicate that the GS dysfunction is associated with various neurological disorders, including traumatic brain injury, hydrocephalus, epilepsy, migraine, and Alzheimer’s disease (AD). Meanwhile, the GS also plays a pivotal role in the pathophysiological process of stroke, including brain edema, blood-brain barrier (BBB) disruption, immune cell infiltration, neuroinflammation, and neuronal apoptosis. In this review, we illustrate the key anatomical structure of the GS, the relationship between the GS and the meningeal lymphatic system, the interaction between the GS and the BBB, and the crosstalk between astrocytes and other GS cellular components. In addition, we contribute to the current knowledge about the role of the GS in the pathology of stroke and the role of AQP4 in stroke. We further discuss the potential use of the GS in early risk assessment, diagnostics, prognostics, and therapeutics of stroke.